2017
DOI: 10.1039/c7ta03552g
|View full text |Cite
|
Sign up to set email alerts
|

A rGO–CNT aerogel covalently bonded with a nitrogen-rich polymer as a polysulfide adsorptive cathode for high sulfur loading lithium sulfur batteries

Abstract: A covalently bonded polyethylenimine–rGO–MWCNT composite achieves outstanding performance at an ultra-high sulfur loading of up to 18 mg cm−2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 52 publications
3
38
0
Order By: Relevance
“…As we study Figure a,b together, we need to understand that an advanced lithium–sulfur cell with all three necessary parameters (i.e., high sulfur loading, high sulfur content, and low electrolyte sulfur ratios) is possible, but it is also full of challenges. Over the last two years, more and more studies have pointed out the problems of making a sulfur cathode with both high sulfur loading and content within a cell with a low electrolyte/sulfur ratio, including low sulfur utilization, inferior discharge/charge efficiency, and short cycle life . By studying the electrochemical inefficiency and instability, researchers have proposed several possible solutions.…”
Section: Extrinsic Challenges Of Fabricating High‐loading Sulfur Cathmentioning
confidence: 99%
See 3 more Smart Citations
“…As we study Figure a,b together, we need to understand that an advanced lithium–sulfur cell with all three necessary parameters (i.e., high sulfur loading, high sulfur content, and low electrolyte sulfur ratios) is possible, but it is also full of challenges. Over the last two years, more and more studies have pointed out the problems of making a sulfur cathode with both high sulfur loading and content within a cell with a low electrolyte/sulfur ratio, including low sulfur utilization, inferior discharge/charge efficiency, and short cycle life . By studying the electrochemical inefficiency and instability, researchers have proposed several possible solutions.…”
Section: Extrinsic Challenges Of Fabricating High‐loading Sulfur Cathmentioning
confidence: 99%
“…Unfortunately, there is no clear direction for solving the deterioration of lithium–sulfur cycle life and stability. However, cathodes fabricated with a 3D current collector could have longer cycle lives of between 100 to 200 cycles (Table S2) . It is understandable that the 3D conductive matrix enables the resulting cathode to possess inner conductive pathways for facilitating fast charge transfer and to have a polysulfide reservoir for reducing the loss of active material .…”
Section: Extrinsic Challenges Of Fabricating High‐loading Sulfur Cathmentioning
confidence: 99%
See 2 more Smart Citations
“…53 Thus, the attention on designing host materials for sulfur cathodes has extended from physical confinement to surface chemistry. [54][55][56][57][58] That is, the confinement barrier should not only trap the solvated polysulfides but also provide subsequent surface redox centers for the adsorbate. Aurbach et al reported a groundbreaking work in which redox mediators were introduced to enable the application of Li 2 S cathodes for Li-S batteries.…”
mentioning
confidence: 99%